The Design of Final Project Information System - Afnil Dwi Oktanto; Palgunadi Surya Prasetyo; Irwan Irwan; Linda Fujiyanti (Universitas Multimedia Nusantara, 2021)
The final project is an educational method to determine the competence of a student regarding the knowledge that has been obtained during lectures. The Final Project Information System is carried out in accordance with the General Guidelines for the Final Project of the Bangka Belitung Manufacturing Polytechnic, the final project data management process is managed by the final project commission. The implementation of the final project information is currently still being done manually. Making a website-based Final Project Information System aims to make the final project implementation process more efficient and effective. The actors involved in it are students, final project commissions, supervisors, and examiners. In this research, the method used is the development of the Software Development Lifecycle method.